Exocrine pancreatic insufficiency and causes of abdominal symptoms in diabetes patients - Roland Kadaj-Lipka; Grażyna Rydzewska (Gastroenterology Review)
The pancreas has dual functions, endocrine and exocrine, that complement each other and work closely together, contributing to the digestion, absorption, and metabolism of foods. More than a decade ago, it was demonstrated that pancreatic exocrine insufficiency occurs in a significant number of patients with diabetes mellitus. Diabetes mellitus affects virtually every organ system in the body, and the degree of organ involvement depends on the duration and severity of the disease, as well as other co-morbidities. Gastrointestinal side effects include pancreatopathy, small intestinal bacterial overgrowth, oesophageal dysmotility, gastroesophageal reflux disease, gastroparesis, neuropathy, and nonalcoholic fatty liver disease.